The use of exercise-based videogames for training and rehabilitation of physical function in older adults: current practice and guidelines for future research. (June 2012) - Smith, Stuart T; Schoene, Daniel
Declines in physical or cognitive function are associated with age-related impairments to overall health. Functional impairment resulting from injury or disease contribute to parallel declines in self-confidence, social interactions and community involvement. Fear of a major incident such as a stroke or a bone-breaking fall can lead to the decision to move into a supported environment, which can be viewed as a major step in the loss of independence and quality of life. Novel use of videogame console technologies are beginning to be explored as a commercially available means for delivering training and rehabilitation programs to older adults in their own homes. We provide an overview of the main videogame console systems (Nintendo Wii™, Sony Playstation ® and Microsoft Xbox ® ) and discuss some scenarios where they have been used for rehabilitation, assessment and training of functional ability in older adults. In particular, we focus on two issues that significantly impact functional independence in older adults, injury and disability resulting from stroke and falls.